Pengaruh Net Profit Margin, Current Ratio, dan Debt to Equity Ratio terhadap Return on Asset pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di BEI Periode 2021-2024 - Dian Novita Sari Pane; Hadi Suriono (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to analyze the effect of NPM, CR, and DER on ROA in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research uses a quantitative approach with secondary data obtained from the companies’ financial statements published on the official website of the Indonesia Stock Exchange. The sampling technique used purposive sampling, resulting in 11 companies with a total of 44 observations. Data analysis was conducted using multiple linear regression with the assistance of the SPSS program, starting with classical assumption tests followed by partial and simultaneous hypothesis testing. The results show that partially NPM has a positive and significant effect on ROA, CR has no significant effect on ROA, while DER has a negative and significant effect on ROA. Simultaneously, NPM, CR, and DER have a significant effect on ROA. The coefficient of determination value of 0.821 indicates that the independent variables explain 82.1% of ROA, while the remaining 17.9